2015
DOI: 10.24059/olj.v19i3.675
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Empirical Studies on Participants’ Interactions in Internet-Mediated Discussion Boards as a Course Component in Formal Higher Education Settings

Abstract: This systematic review and synthesis of existing empirical studies examines peer-reviewed research articles published between January 2000 and May 2014 on the use of Internet-mediated discussion boards in higher education settings with a specific interest in the participants' interactions. Forty-two primary studies were examined after a systematic search and full text review. The findings from the primary studies regarding participants' interactions were analyzed using constant comparison coding techniques. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Most students did not feel comfortable to openly challenge their peers. The study conducted by Zhou (2015) found that students rarely challenged or disagreed with their peers in online discussion postings. It was understanding that students might be afraid to offend their peers.…”
Section: Considerations For Redesignmentioning
confidence: 99%
“…Most students did not feel comfortable to openly challenge their peers. The study conducted by Zhou (2015) found that students rarely challenged or disagreed with their peers in online discussion postings. It was understanding that students might be afraid to offend their peers.…”
Section: Considerations For Redesignmentioning
confidence: 99%
“…Several modern computer-mediated communication (CMC) technologies can be utilized in online courses for the purpose of increasing collaborative interactions among the participants. Concurrently, the use of an asynchronous discussion forum (DF) is increasing in asynchronous Computer Science Students' Attitudes Towards the Use of Structured and Unstructured Discussion Forums in Fully Online Courses online learning (Fear & Brown, 2014;Zhou, 2015). Asynchronous DFs play a substantial role in humanizing online courses by replicating the classroom experience of information exchange and community building, not just between students and their instructor but also among the students themselves (Saadé & Huang, 2009).…”
Section: Computer Science Students' Attitudes Towards the Use Of Strumentioning
confidence: 99%
“…In response to the first question about what they liked, the emergent themes were related to a discussion board as a safe environment, thinking critically and learning from different perspectives, and general praise for the activity. One of the purported benefits of an asynchronous discussion is that it can serve as a safe environment for those participants shy or unwilling to speak out in a face-to-face discussion (Zhou, 2015). One participant noted that it provided the opportunity to think about and discuss the topic freely within this "safe environment".…”
Section: Survey Resultsmentioning
confidence: 99%